(untitled) (International journal of artificial intelligence, 2025)
The rapid expansion of social networks has significantly influenced the global education landscape. While these platforms offer vast opportunities for knowledge acquisition, they also pose challenges to the moral and ethical development of adolescents. This paper explores the mechanisms by which social networks impact the moral and ethical immunity of adolescent students and suggests strategies for fostering resilience in this digital age.